Advantage and validation of vendor‐independent software for myocardial strain analysis compared to vendor‐specific software. Issue 1 (14th October 2020) - Chamberlain, Robert; Shiino, Kenji; Scalia, Gregory M.; Sabapathy, Surendran; Chan, Jonathan
Abstract: Introduction: One of the main limitations incorporating strain imaging into widespread clinical practice is inter‐vendor incompatibility. This poses a problem when serial strain measurements are required in a multi‐vendor echocardiography laboratory. Methods: This study sought to compare the variability of two‐dimensional speckle‐tracking global and regional longitudinal strain using vendor‐specific software and vendor‐independent software from images acquired by two different commercially available ultrasound systems. Forty subjects underwent two sequential echocardiographic acquisitions using different ultrasound systems (GE Vivid E9 and Philips iE33). Global longitudinal strain and regional peak longitudinal strain were derived using vendor‐specific software (EchoPAC BT 13 v201 and QLAB version 10.3) and vendor‐independent software (TomTec Image Arena version 4.6). Agreement and reproducibility of global and regional strain between vendor‐specific and vendor‐independent software were assessed by independent blinded observers. Results: Global longitudinal strain derived from vendor‐independent software was comparable to global longitudinal strain derived from vendor‐specific software, whilst regional strain was lower in agreement compared to global longitudinal strain. There was good overall agreement and high inter‐ and intra‐observer reproducibility using vendor‐independent software for global longitudinal strain and regional strain. Conclusions: Vendor‐independent software provides good agreement with vendor‐specific software for global longitudinal strain. However, minor variability exists for regional strain measurements between vendor‐independent and vendor‐specific software. Good agreement of strain measurements derived by vendor‐independent software suggests vendor‐independent software could potentially be useful for serial follow‐up of global longitudinal strain.